THE IMPACT OF TAX HOLIDAYS ON CORPORATE PERFORMANCE IN INDIA - Sathyanarayana Gowda.V,; Archana H., (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Tax holidays serve as a crucial fiscal policy instrument employed by the Indian government to drive economic growth, attract investment, and enhance corporate performance. These temporary exemptions from tax obligations are strategically designed to encourage businesses to expand operations, invest in infrastructure, and foster innovation. Particularly beneficial for industries such as manufacturing, technology, renewable energy, and special economic zones (SEZs), tax holidays provide financial relief that enhances corporate profitability and competitiveness. A key advantage of tax holidays is their role in boosting foreign direct investment (FDI). By reducing the financial burden on multinational corporations, India positions itself as an attractive destination for global enterprises. This, in turn, leads to job creation, technology transfer, and skill development, significantly contributing to the country’s economic progress. Additionally, tax holidays play a vital role in promoting regional development by incentivizing businesses to establish operations in economically weaker areas, thereby reducing urban-rural economic disparities. However, while tax holidays offer substantial economic benefits, they also present challenges. One major concern is the potential revenue loss for the government, which may impact public expenditure on infrastructure and welfare programs. Furthermore, the uneven distribution of benefits often favors large corporations over small and medium enterprises (SMEs), leading to market imbalances. Additionally, businesses may face financial strain when tax exemptions expire, potentially affecting long-term sustainability. In conclusion, tax holidays have played a pivotal role in shaping corporate performance in India by driving investments, enhancing profitability, and fostering economic development. However, to maximize their effectiveness, a well-structured regulatory framework is essential to ensure equitable benefits distribution while safeguarding fiscal interests. Striking a balance between incentivizing businesses and maintaining government revenue is key to optimizing the long-term impact of tax holidays on corporate performance in India.